(0D/3D) MoS2 on porous graphene as catalysts for enhanced electrochemical hydrogen evolution. (September 2017) - Liu, Yizhe; Zhu, Yuanzhi; Fan, Xiaobin; Wang, Shaobin; Li, Yang; Zhang, Fengbao; Zhang, Guoliang; Peng, Wenchao
Abstract: A new composite material consisting of 0D MoS2 nanodots and 3D MoS2 nano-flowers grown on porous reduced graphene oxide (P-rGO) was synthesized via a two-step process. The P-rGO with a surface area of 759 m 2 g −1 was obtained by CO2 activation of reduced graphene oxide (rGO) at 800 °C. MoS2 was then grown on the P-rGO under hydrothermal conditions. Compared to the nonactivated rGO, P-rGO has functional pores for deposition of MoS2 nanodots and less charge transfer resistance, which can provide more active sites for hydrogen generation, thus leading to the improved activity of (0D/3D) MoS2 /P-rGO in hydrogen evolution reaction (HER). The overpotential of (0D/3D) MoS2 /P-rGO was only ∼150 mV vs. RHE, and the corresponding Tafel slope was ∼56 mV Dec −1, which is comparable to most of the present MoS2 /Graphene HER catalysts. The (0D/3D) MoS2 /P-rGO exhibits as an efficient noble metal free HER catalyst, and has great potential for the electrochemical hydrogen production. Graphical abstract: